Pengaruh Budaya Organisasi dan Lokus Pengendalian Internal terhadap Kreativitas Pegawai PT Surveyor Indonesia (Persero) Di Jakarta - Muhammad Taufik Hadi Saputra; Abdul Rohman; Titik Untari (Jurnal Syntax Transformation, 2021)
This research aims to analyze the influence of Organizational Culture and Control Locus on the reativity of C employees of PT Surveyor Indonesia (Persero) in Jakarta. The research method used is a survey method with several linear regression techniques. The population consists of permanent employees of PT Surveyor Indonesia (Persero) in Jakarta which amounted to 437 people. The sampling technique used is Simple Random Side with Slovin formula, margin of error of 0.1 or 10%. First, the analysis results for the partial test (test t) on the Organizational Culture variable obtained a count of t 2,736> ttabel (1,990) with a probability value of 0.000, meaning that it was smaller than 0.05, so Ho was rejected and Ha was accepted, meaning that organizational culture had a positive effect. Second, the analysis results for partial tests (t tests) on the locus of control variables obtained tcount 4,819> ttable (1,990) with a probability value of 0.008, which means less than 0.05, so Ho is rejected and Ha is accepted, meaning that the control locus has a positive effect. Third, the results of the analysis for the simultaneous test obtained by Fcount> Ftabel, which is 14,868> 3,112 and the significance value of 0.000 <0.05. The determining coefficient or contribution of X1 and X2 to Y is R Square = 0.364. Which means that 36.4% of the variation in creativity (Y) can be explained by organizational culture and locus control. The remaining 63.6% was explained by other variables not used as ingredients in the study. To test this hypothesis, Ho was rejected and Ha accepted, meaning that the regression coefficient is significant or it can be said that simultaneously there are significant effects of Organizational Culture and Locus Control on Creativity. It can be concluded that the creativity of employees of PT Surveyor Indonesia (Persero) in Jakarta is positively and significantly influenced by organizational culture and locus control both partially and simultaneously. Therefore, to increase the creativity of employees of PT Surveyor Indonesia (Persero) in Jakarta, it can be done by improving organizational culture and locus control.